Finance and Development, September 1968. (Finance and Development; Finance and Development, 1968)
This paper describes development of the agriculture sector in Northwest Mexico. The paper highlights that owing to the projects in the river valleys of the northwest and others throughout the country, Mexico grows enough to feed itself and to export in substantial quantity. A third of the crops are produced on the 13 percent of cultivable area now under irrigation. The engineers of Hydraulic Resources are proud of their achievements; they have the visual evidence and the statistics to prove the importance of their contribution to Mexico.